A "Greenprint" for International Cooperation on Climate Change - Mattoo, Aaditya; Subramanian, Arvind (World Bank, Washington, DC, 2013)
International negotiations on climate change have been dogged by mutual recriminations between rich and poor countries, constricted by the zero-sum arithmetic of a shrinking global carbon budget, and overtaken by shifts in economic power between industrialized and developing countries. To overcome these "narrative," "adding-up," and "new world" problems, respectively, this paper proposes a new Greenprint for cooperation. First, the large dynamic emerging economies -- China, India, Brazil, and Indonesia -- must assume the mantle of leadership, offering contributions of their own and prodding the reluctant industrial countries into action. This role reversal would be consistent with the greater stakes for the dynamic emerging economies. Second, the emphasis must be on technology generation. This would allow greater consumption and production possibilities for all countries while respecting the global emissions budget that is dictated by the climate change goal of keeping average temperature rise below 2 degrees centigrade. Third, instead of the old cash-for-cuts approach -- which relies on the industrial countries offering cash (which they do not have) to the dynamic emerging economies for cuts (that they are unwilling to make) -- all major emitters must make contributions. With a view to galvanizing a technology revolution, industrial countries would take early action to raise carbon prices. The dynamic emerging economies would in turn eliminate fossil fuel subsidies, commit to matching carbon price increases in the future, allow limited border taxes against their own exports, and strengthen protection of intellectual property for green technologies. This would directly and indirectly facilitate such a technological revolution.